The Effect of Liquidity, Leverage and Profitability on Company Value of Healthcare Sector Businesses listed in the Indonesia Stock Market - Yulazri Yulazri; Febrizqia Ramadianty Joefatha (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research sought to determine the effects of profitability, leverage, and liquidity on the value of healthcare sector businesses listed on the Indonesia Stock Markket for the years 2018-2021. The sample in this research is a number of 10 businesses and after outliers were made there were 9 businesses with a total sample data that met the research criteria as many as 36 financial reports. The sampling techniqueÂ is to use purposive sampling technique. The approach to data analysis which is multiple linear regression, SPSS is used for the analysi. The hypothesis test reveals that leverage has no effect on company value, while liquidity and profitability have a positive impact.